Determinan Kepatuhan Wajib Pajak Pelaku Usaha E-Commerce : Usaha Mikro dan Kecil D.I.Yogyakarta - Muhammad Kais; Dekar Urumsah (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
Taxpayer non-compliance in carrying out their tax obligations is still a serious problem in Indonesia. Various efforts have been made and attempted by the government to increase taxpayer compliance, but the results obtained have not been as expected. This research aims to propose a conceptual model to determine the factors that influence taxpayer compliance in e-commerce businesses by connecting tax knowledge, tax sanctions and religiosity with gender and age of the business as moderators. It is hoped that the conceptual model from this research can provide useful information for the government and the wider public about the factors that influence taxpayer compliance so that in the future it can increase taxpayer compliance.